Development of a Blockchain based energy trading scheme for prosumers - Artur Pinto Almeida (2020)
Throughout the last few years, the electric market has undergone countless changes due to the continuous demand growth, the introduction of Information and Communication Technologies (ICT) on the network level, and the introduction of distributed generation sources, including household appliances that turned some consumers into a new category, prosumers. This way, the energy systems have become more decentralized through the development of the Internet of Things (IoT) which can allow for the creation of smart grids. Along with this transformation, there is also a change underway concerning consumer panorama as they become more central to the operations of the electric system. The introduction of all these technologies grants the prosumer the ability to participate more actively in the electric market, especially on the decentralization viewpoint, where each user contribute to the stability of the system operation. From this aspect, an interesting technology is the blockchain, which has revealed itself to have a huge potential in other areas, such as the financial sector. The research for the use of blockchain in the electric system has been due to its several promising characteristics. Namely, on account of its distributed and immutable nature which provides the potential to accelerate the transition of the electric market to a more digital and decentralized system. In this thesis, the blockchain capacities will be researched and adapted to develop of a scheme of energy transactions on the prosumer level. This will be done through the creation of a virtual market based on smart contracts, using the Solidity language in a remix environment, which will also allow consumers and energy producers to communicate between each other, exchanging tokens for electricity to satisfy the needs of all the evolved community. The use of blockchain will then make it possible for the creation of autonomous processes, allowing the system users to exchange energy, in a reliable and secure way, without the need of a third party.